KARAKTERISTIK FISIK DAN KIMIA TEPUNG HANJELI (Coix lacryma-jobi L.) YANG DIMODIFIKASI DENGAN NA2S2O5 DAN APLIKASINYA PADA CUPCAKE: Characterization of the Hanjeli (Coix lacryma-jobi L) Modified Starch with Sodium Metabisulfite (Na2S2O5) and Its Application on Cupcake - Mrr Lukie Trianawati; CC Nurwitri; Titi Risnawati; Sri Rejeki; Rosy Hutami (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2022)
Hanjeli seeds are one of the typical Indonesian cereals that have great potential but their utilization is not optimal. In West Java, generally hanjeli seeds are only made into porridge and lunkhead. In this study, hanjeli seeds were processed into modified flour which was used to substitute wheat flour in the formulation of cupcake products. Modified hanjeli flour is produced from the following process, when raw hanjeli seeds are soaked in sodium metabisulfite (Na2S2O5) at concentrations of 50, 75 and 100 ppm for 36 hours, steamed, roasted, ground and sieved. The selected modified hanjeli flour was hanjeli flour with 75 ppm Na2S2O5 immersion which had a protein content of 13.35%. Furthermore, hanjeli flour is processed into cupcakes. The proportions of hanjeli flour substitution used in making cupcakes were 10, 20 and 30%. The cupcakes that have been produced are then tested hedonic (preferred). Based on these tests, it is known that the cupcake that has the highest score is the 10% modified hanjeli flour cupcake. Based on the results of the description test, it is known that the values ​​for the parameters of color brightness are 5.19 (slightly bright), sweetness level is 5.19 (slightly sweet), vanilla flavor sharpness is 5.42 (slightly sharp), vanilla aroma sharpness is 4.96 (ordinary) softness. the texture is 5.08 (slightly soft), the wetness of the crumb is 5.12 (slightly wet), and the elasticity of the texture is 5.00 (slightly chewy). ABSTRAKBiji Hanjeli merupakan salah satu serealia khas Indonesia yang sangat potensial tetapi pemanfaatannya belum optimal. Di Jawa Barat, umumnya biji hanjeli hanya dibuat bubur dan dodol. Dalam penelitian ini biji hanjeli diolah menjadi tepung modifikasi yang digunakan untuk mensubtitusi tepung terigu dalam formulasi produk cupcake. Tepung hanjeli modifikasi dihasilkan dari proses berikut biji hanjeli mentah direndam dengan Natrium metabisulfit (Na2S2O5) dengan konsentrasi 50, 75 dan 100 ppm selama 36 jam, dikukus, dioven, digiling dan diayak. Tepung hanjeli modifikasi yang terpilih adalah tepung hanjeli dengan perendaman 75 ppm Na2S2O5 yang memiliki kadar protein 13,35%. Selanjutnya tepung hanjeli diolah menjadi cupcake. Proporsi substitusi tepung hanjeli yang digunakan dalam pembuatan cupcake adalah 10, 20 dan 30%. Cupcake yang telah dihasilkan kemudian diuji hedonik (kesukaan). Berdasarkan uji tersebut diketahui bahwa cupcake yang memiliki skor tertinggi yaitu cupcake 10% tepung hanjeli modifikasi. Berdasarkan hasil uji deskripsi diketahui bahwa nilai untuk parameter kecerahan warna 5,19 (agak cerah), tingkat kemanisan 5,19 (agak manis), ketajaman rasa vanilla 5,42 (agak tajam), ketajaman aroma vanilla 4,96 (biasa) kelembutan tekstur 5,08 (agak lembut), kebasahan crumb 5,12 (agak basah), dan kekenyalan tekstur 5,00 (agak kenyal).